An example of peripheral neuropathy that can be managed by the general practitioner: peroneal nerve neuropraxia (Portuguese Journal of Family Medicine and General Practice, 2021)
Introduction: Neuropraxia is a rare form of peripheral nerve injury. All general practitioners (GP) can manage this condition due to its excellent prognosis and complete reversibility.Case Description: 46-year-old male, had cholecystectomy for gallstones in February 2019, having lost 10 kg. On the 18th of November 2019, he presented to his GP with an inability to lift his left foot, accompanied by hypoesthesia and decreased strength in the entire left lower limb since the 11th of September 2019, after being seated for three hours, with his right leg crossed over the left. The GP requested an electromyogram test, which revealed neuropraxia of the left peroneal nerve. All symptoms disappeared spontaneously six months after the initial injury.Comment: Although reversible, neuropraxia has a very exuberant clinical presentation and can lead the patient to think that suffers from a serious illness. Knowing how to approach and make sure that the patient understands the disease and its prognosis is essential to avoid overdiagnosis and overtreatment.
Keywords: Peripheral neuropathy; Peroneal nerve; Neuropraxia